Administration of improvements in matrix income management for better performance - Tofoli, Eduardo Teraoka; Santos, Andre Ponce dos; Tófoli, Irso; Silva, Íris Bento da (Revista Gestão da Produção Operações e Sistemas, 2008)
Companies that sell their products in markets in fierce competition must have resources or tools that help in analysis and control, and have the objective of verifying whether the company is reaching expected results, if it is meeting its targets in a given period, or if it is experiencing problems with sales and needs to take remedial action. It is necessary for businesses that identify with this scenario of competition to acquire, or even create, machinery or tools to help in Matrix Income Management. These tools are used at a refrigerator company, in the whole group and in every segment in which it operates, which helps in strategic planning in maximizing revenues through sales, and the realization of profit. This tool is based on three pillars: commercial organization as a whole, customers and production. If any problem occurs in one of the three pillars, the tool identifies it, making it much easier to resolve these problems by those responsible for managing them. The company that uses this tool can more easily achieve its goals. Key-Words: Administration of Improvement; Matrix Income Management; Performance.